Changing control and accounting in an African gold mine: An emergence of a new despotic control. Issue 2 (5th June 2017) - Tsamenyi, Mathew; Hopper, Trevor; Uddin, Shahzad
Abstract : Purpose: The paper aims to examine accounting changes in the Ashanti Gold Corporation (AGC) in Ghana over 120 years from pre-colonialism to recent times and whether the framework of management accounting transformations in Hopper et al. (2009) is applicable. Design/methodology/approach: Mixed data sources are used, namely, interviews, some observations of practices, historical documentation, company reports and research papers and theses. The results are categorised according to the periods and contextual factors in the Hopper et al. framework to test whether it matches the data collected. Findings: Despotic controls with minimal management accounting but stewardship accounting to the head office in London prevailed under colonialism. Upon independence state, capitalist policies descended into politicised state capitalism. Under nationalisation, the performance of mines deteriorated, and accounting became decoupled from operations. In the early 1980s, fiscal crises forced Ghana's government to turn to the World Bank and International Monetary Fund for loans. This period marked a gradual transformation of AGC into a foreign multinational, organised along divisional lines and currently exercises despotic control through supply chain management that renders labour precarious and is neglectful of corporate social accounting issues. Research limitations/implications: The work challenges neo-classical economic prescriptions and analyses of accounting in developed countries by indicating its neglect of the interests of other stakeholders, especially labour and civil society. Accounting is important for development but the article infers other forms may better serve the public interest. Originality/value: The paper tests the Hopper et al. framework with respect to a large private multinational in the commodity sector over an extended period, which differs from the case studies drawn on originally.